A novel de novo PDE4D gene mutation identified in a Chinese patient with acrodysostosis. Issue 11 (14th September 2019) - Zhan, Yongkun; Chen, Weicheng; Feng, Zhiyu; Tan, Chaozhong; Li, Mengru; Song, Yangliu; Zhao, Zhengshan; Sheng, Wei; Huang, Guoying
Summary: Acrodysostosis is an extremely rare disorder at birth, that is, characterized by skeletal dysplasia with short stature and midfacial hypoplasia, which has been reported to be caused by PDE4D and PRKAR1A gene mutations. Here, a Chinese boy with acrodysostosis, ventricular septal defect, and pulmonary hypertension was recruited for our study, and his clinical and biochemical characteristics were analyzed. A novel de novo heterozygous missense mutation (NM_001104631: c.2030A>C, p.Tyr677Ser) of the PDE4D gene was detected by whole exome sequencing and confirmed by Sanger sequencing. The c.2030A>C (p.Tyr677Ser) variant was located in exon 15 of the PDE4D gene, predicted to be damaging by a functional prediction program and shown to be highly conserved among many species. Further functional analysis showed that the p.Tyr677Ser substitution changes the function of the PDE4D protein, affects its subcellular localization in transfected cells, increases PDE4 activity in the regulation of cAMP signaling and affects cell proliferation. Our study identified a novel de novo PDE4D mutation in acrodysostosis of Chinese origin that not only contributes a deeper appreciation of the phenotypic characteristics of patients with PDE4D mutations but also expands the spectrum of PDE4D mutations.